If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 3(4x + -1) + -19x = 9 Reorder the terms: 9x + 3(-1 + 4x) + -19x = 9 9x + (-1 * 3 + 4x * 3) + -19x = 9 9x + (-3 + 12x) + -19x = 9 Reorder the terms: -3 + 9x + 12x + -19x = 9 Combine like terms: 9x + 12x = 21x -3 + 21x + -19x = 9 Combine like terms: 21x + -19x = 2x -3 + 2x = 9 Solving -3 + 2x = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 2x = 9 + 3 Combine like terms: -3 + 3 = 0 0 + 2x = 9 + 3 2x = 9 + 3 Combine like terms: 9 + 3 = 12 2x = 12 Divide each side by '2'. x = 6 Simplifying x = 6
| 4(-2x+3)=5x | | 1636.9997=1/3(691.69)(h) | | 3.2-9x+7.1-3x=10.3-12x | | 3x+y-3z=2 | | 13x-3=10x+3 | | 8x-7+9(x-2)=26 | | 15+9X+3(2X-20)=0 | | T=0.2(43) | | 3(2x-1)-5x=8 | | T=0/2(43) | | 3x-13=52 | | -.75x+29=-37 | | 6x+X=-2+17 | | 2010.6048=2*3.14*8.7*8.7+2*3.14*8.7*h | | 2n+8=6n+24 | | 5x+38=x+18 | | 7x-65=x/2 | | -1.3b= | | (3tan^2)2x-3=0 | | -1/1×3/9 | | (6a+8b)(-2)= | | 7x-4x=X-4 | | (2/13x)=(1/3) | | 3318.1008=2*3.14*r*r+2*3.14*r*36.5 | | [(3x)^4]/[81(x^-2)^-2] | | 2(3X-4)+5X=58 | | 2x-6(2-x)=12 | | 2x+3y-4+x^2-5y+8= | | t^2=2.3-0.5 | | 2N-16=3(2N-16)-6 | | y=6x+ax+b | | 27-6(8)+17= |